A Choice‐Based Screening Method for Compulsive Drug Users in Rats. Issue 1 (15th July 2013) - Lenoir, Magalie; Augier, Eric; Vouillac, Caroline; Ahmed, Serge H.
Abstract: We describe a protocol for screening compulsive drug users among cocaine self‐administering rats, the most frequently used animal model in addiction research. Rats are first trained on several alternating days to self‐administer either cocaine (i.v.) or saccharin‐sweetened water (by mouth)—a potent, albeit nonessential, nondrug reward. Then rats are allowed to choose between the two rewards over several days until the preference stabilizes. Most rats choose to stop using cocaine and pursue the alternative reward. Only a minority of Wistar strain rats (generally 15%) persist in taking the drug, regardless of the severity of past cocaine use and even when made hungry and offered the possibility to relieve their physiological need. Persistence of cocaine use in the face of a high‐stakes choice is a core defining feature of compulsion. This choice‐based screening method for compulsive drug users is easy to implement, has several important applications, and compares well with other methods in the field. Curr. Protoc. Neurosci . 64:9.44.1‐9.44.17. © 2013 by John Wiley & Sons, Inc.